2002
DOI: 10.1557/jmr.2002.0194
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzed Water as an Alternative for Environmentally Benign Semiconductor Cleaning

Abstract: The present semiconductor cleaning technology is based upon RCA cleaning [W. Kern and D.A. Puotinen, Cleaning Solutions Based on Hydrogen Peroxide for use in Silicon Semiconductor Technology (RCA Rev., 1970) pp. 187-206], a high-temperature process that consumes vast amounts of chemicals and ultrapure water (UPW) [T. Futatsuki, T. Imaoka, Y. Yamashita, and K. Mitsumori, J. Electrochem. Soc., 142, 966 (1995)]. Therefore, this technology gives rise to many environmental issues, and some alternatives such as ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The hydrophobicity of the fruit surface decreased when washed with AEW since it acts as a surfactant. Consequently, any microorganisms on the surface of the fruit could be easily accessed, and a high reduction of levels of microbial populations would thus be achieved (Ryoo, Kang, & Sumita, 2002). It was also reported that pH of cathodic solutions can be stable for at least three days, and the pH stability provides a long lasting inhibitory effect.…”
Section: Changes In Physicochemical Properties and Microbial Inactimentioning
confidence: 99%
“…The hydrophobicity of the fruit surface decreased when washed with AEW since it acts as a surfactant. Consequently, any microorganisms on the surface of the fruit could be easily accessed, and a high reduction of levels of microbial populations would thus be achieved (Ryoo, Kang, & Sumita, 2002). It was also reported that pH of cathodic solutions can be stable for at least three days, and the pH stability provides a long lasting inhibitory effect.…”
Section: Changes In Physicochemical Properties and Microbial Inactimentioning
confidence: 99%
“…The one drawback of the E-sulfuric acid process is that electrolysis needs to be conducted at temperatures below 90 • C and the product from the electrolysis cell has to be heated to achieve temperatures attainable in conventional SPM. 17 18 Oxygen and hydrogen dissolved water produced in anode and cathode compartments of an electrolysis cell has shown some promise for cleaning. 18 Such water is termed 'Electrolyzed Water' and is generated in an apparatus shown schematically in Figure 12.…”
Section: Electrochemical Generation Of Cleaning Chemicalsmentioning
confidence: 99%
“…17 18 Oxygen and hydrogen dissolved water produced in anode and cathode compartments of an electrolysis cell has shown some promise for cleaning. 18 Such water is termed 'Electrolyzed Water' and is generated in an apparatus shown schematically in Figure 12. The apparatus consists of three chambers: anode, cathode, and middle.…”
Section: Electrochemical Generation Of Cleaning Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 As substrate sizes of silicon wafer or glass plate increase, the number of cleaning process steps increases so that the amount of chemicals and ultrapure water ͑UPW͒ consumed in the RCA cleaning process increases drastically and production cost and environmental burden increase as well. In order to resolve these issues, several alternatives to functional waters, such as hydrogenated ultrapure water, 6 ozonized water, 7,8 and electrolyzed water, [9][10][11][12] have been studied. However, their applications have not overcome the two-step RCA concept as mentioned above.…”
mentioning
confidence: 99%